A Biomechanical Comparison of Composite Fixation and Veterinary Acetabular Plates for Stabilization of Acetabular Osteotomies in Dogs Loaded in Three-Point-Bending Fashion - Ianz, O. I.; Lewis, D. D.; Madison, J. B.; Blaeser, L. L. (Veterinary and Comparative Orthopaedics and Traumatology, 1998)
An in vitro study comparing the biomechanical performance and accuracy of reduction for two methods of acetabular osteotomy repair in the dog is presented. Pelves were harvested from five adult mixed breed dogs weighing 25-30 kg. On e hemipelvis from each dog was repaired with the composite fixation and the contralateral hemipelvis was repaired with a 2.0 mm six hole veterinary acetabular plate. Eac h hemipelvis was loaded in a threepoint- bending fashion at a rate of 5 mm/min. An extensometer was placed over the dorso-medial surface of the acetabular osteotomy during loading. Reduction was significantly better for hemipelves stabilized with the composite fixation when compared to hemipelves stabilized with the 2.0 mm six hole veterinary acetabular plate. There was not a significant difference in bending stiffness, distractional stiffness, yield point and maximum load between repair groups.An in vitro comparison was made between a composite fixation method and acetabular plates for the stabilisation of acetabular osteotomies.
Keywords: PMMA; canine acetabular plates; acetabular osteotomy